Pengembangan multimedia berbasis salingtemas untuk pembelajaran IPA tema 1 di kelas IV Sekolah Dasar - Fitrian Prila Wardani; Dita Puspitawedana; Pebri Isnawati (Navigation Physics : Journal of Physics Education, 2019)
This research is a Research Development (R&D) using design research. The purpose of this study is to develop and know the feasibility of Salingtemas-based multimedia (Science, Environment, Technology, and Society) for learning science theme 1 in grade IV of Elementary School. The stage carried out in this research is in the initial stages resulting in a description of the need for multimedia development. At the development stage begins by designing solutions to problems found in the initial stages. The evaluation phase is carried out an evaluation (validation test and product trial) to determine the feasibility and improve the product that has been developed. The subjects of the trial are teachers and fourth grade students in the SD Negeri 2 Cihonje, Gumelar subdistrict, Banyumas district. Testing the feasibility of multimedia based on Salingtemas is carried out with an assessment by experts both in terms of material and media that have been developed. The results show that the development of multimedia based on Salingtemas for natural science learning theme 1 in class IV Elementary School reach an average percentage of 89,5% for media expert judgment, 91% for material expert assessment and 85% for users, so it can be stated worthy.